Full-perovskite laminated solar cell and preparation method thereof
By introducing a perovskite absorbing layer modified by covalent organic skeleton material into perovskite stacked solar cells, a three-dimensional network structure is formed, which solves the problems of low photoelectric conversion efficiency and poor stability of traditional solar cells, and achieves more efficient More stable solar cell performance has promoted the development of solar cell technology.
Patent Information
- Application Number
- CN202411412707.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional solar cells have problems such as low photoelectric conversion efficiency, poor stability and insufficient durability, which limits their large-scale applications.
Adopt a full perovskite stacked solar cell structure, including a tunnel junction between a wide bandgap perovskite battery and a narrow bandgap perovskite battery, and introduce covalent organic framework materials into the perovskite absorption layer, which are formed by heat treatment. Three-dimensional network structure to improve battery performance.
It improves the photoelectric conversion efficiency and stability, enhances the utilization rate of the solar spectrum, extends the service life of the battery, and meets the high standards for commercial applications.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to an all-perovskite stacked solar cell and a preparation method thereof. Background Art
[0002] As a clean and renewable energy source, the development and utilization of solar energy has received widespread attention. As a key technology for converting solar energy into electrical energy, the efficiency and stability of solar cells are important factors that determine their commercial application prospects. Traditional single-junction solar cells often have low photoelectric conversion efficiency due to the limitations of the band gap of light-absorbing materials. In order to improve the photoelectric conversion efficiency, researchers have developed a variety of new solar cell structures, such as multi-junction solar cells and stacked solar cells. These cells can more effectively utilize the solar spectrum by achieving complementary absorption between different cell layers, thereby improving the overall photoelectric conversion efficiency.
[0003] However, there are still some challenges in the existing tandem solar cell technology, such as high material cost, complex preparation process, poor battery stability and other issues. In addition, the long-term durability of the battery is also one of the key factors restricting its large-scale application. In order to overcome these limitations, researchers are constantly exploring new materials and optimizing preparation processes in order to achieve more efficient, more stable and lower-cost solar cell technology. In this context, the present invention proposes a new type of tandem solar cell and its preparation method, which aims to solve some deficiencies in the prior art in order to promote the development of solar cell technology. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the present invention provides a full perovskite tandem solar cell to solve the shortcomings of traditional solar cells in terms of photoelectric conversion efficiency, stability, durability and solar spectrum utilization.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A full perovskite tandem solar cell, the full perovskite tandem solar cell comprising a wide bandgap perovskite cell and a narrow bandgap perovskite cell and a tunnel junction arranged between the wide bandgap perovskite cell and the narrow bandgap perovskite cell; at least one of the wide bandgap perovskite cell and the narrow bandgap perovskite cell comprises a perovskite absorption layer modified by a covalent organic framework material.
[0007] As a preferred technical solution, the covalent organic framework material modified perovskite absorption layer is obtained by uniformly mixing a perovskite precursor solution and a covalent organic framework material and then subjecting the mixture to heat treatment.
[0008] As a preferred technical solution, the covalent organic framework (COF) material is firstly subjected to an addition reaction of a trivinyl cyclic heterocyclic compound and hydroxyacrylamide, and then the reaction product undergoes a molecular self-assembly reaction with diisocyanate to form a covalent organic framework material with a three-dimensional network structure.
[0009] The ordered porous structure of the COF material of the present application acts as a template in the nucleation and growth process of perovskite crystals, promotes the directional growth of perovskite crystals, and is conducive to the preparation of a more uniform and higher quality perovskite absorption layer, thereby improving the photoelectric conversion efficiency of the battery; in addition, the functional groups of the COF material can interact with the defect sites on the surface of the perovskite, effectively passivate these defects, reduce carrier capture and non-radiative recombination, and thus reduce energy loss; the three-dimensional network structure of the COF material not only provides physical protection for the perovskite absorption layer, resists environmental erosion, and improves chemical stability, but also enhances the extraction and transmission efficiency of carriers, optimizes the energy level structure of the battery, and improves the open circuit voltage and fill factor.
[0010] As a preferred technical solution, the trivinyl cyclic heterocyclic compound is at least one of 2,4,6-trivinyl cycloboroxane, 2,4,6-trimethyl-2,4,6-trivinyl cyclotrisiloxane, and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane. The trivinyl cyclic heterocyclic compound of the present application reacts with the unsaturated bond in the hydroxyacrylamide through the vinyl group to form a cyclic heterocyclic compound with three hydroxyl groups and an amide group, which provides abundant reaction sites for subsequent molecular self-assembly. Further, the hydroxyl group is reacted with the isocyanate group in the diisocyanate to finally form a three-dimensional network structure with porous characteristics. The present application not only enhances the crosslinking density and mechanical strength of the covalent organic framework (COF) material and improves the thermal stability of the material through the introduction of the cyclic heterocyclic compound, but also enhances the interaction between the COF and the perovskite layer through the chemical functionality of the cyclic structure. This enhanced interaction helps to improve the energy conversion efficiency of solar cells, reduce the non-radiative recombination of carriers, and thus improve the overall performance of the battery. In addition, the introduction of cyclic heterocyclic compounds may also promote the nucleation and growth of perovskite crystals, further optimizing the quality and optoelectronic properties of the perovskite absorber layer, allowing solar cells to maintain efficient and stable operation under high temperatures and various environmental conditions.
[0011] As a preferred technical solution, the hydroxyacrylamide is at least one of N-hydroxymethyl acrylamide, N-(2-hydroxyethyl) acrylamide, N-(3-hydroxypropyl) acrylamide, N-(2-hydroxypropyl) methacrylamide, and N-(2-hydroxyethyl) methacrylamide. The present application not only further enhances the chemical functionality of the covalent organic framework (COF) material and the interaction with the perovskite layer by introducing an amide group, thereby further improving the energy conversion efficiency of the solar cell, but also enhances the stability and mechanical properties of the material through the hydrogen bond formation ability of the amide group. In addition, the electronic properties of the amide group can further optimize the electronic structure of the COF material, which helps to improve the open circuit voltage and fill factor of the battery.
[0012] As a preferred technical solution, the diisocyanate is at least one of 4,4'-methylenebis(phenyl isocyanate), p-phenylene diisocyanate, 1,1'-methylenebis(3,5-diethyl-4-isocyanatobenzene), 1,3-phenylenediisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, 1,3-bis(isocyanatomethyl)benzene, m-phenylenediisocyanate, and 1,3-bis(isocyanatomethyl)benzene.
[0013] As a preferred technical solution, the wide bandgap perovskite cell includes a wide bandgap perovskite absorption layer modified by a covalent organic framework material; the wide bandgap perovskite absorption layer is obtained by mixing a wide bandgap perovskite precursor solution and a covalent organic framework material uniformly and then heat treating; the wide bandgap perovskite precursor solution is obtained by mixing methylamine iodide, methyl bromide, lead iodide, cesium iodide, cesium chloride, lead bromide and a solvent. The operating conditions of the heat treatment are annealing at 140-160°C for 30-90 minutes.
[0014] As a preferred technical solution, the narrow-bandgap perovskite cell includes a narrow-bandgap perovskite absorption layer modified by a covalent organic framework material; the narrow-bandgap perovskite absorption layer is obtained by mixing a narrow-bandgap perovskite precursor solution and a covalent organic framework material uniformly and then heat-treating; the narrow-bandgap perovskite precursor solution is obtained by mixing tin powder, methyl iodide, methylamine iodide, lead iodide, stannous iodide, stannous fluoride and a solvent. The operating conditions of the heat treatment are annealing at 80-120°C for 30-60 minutes.
[0015] As a preferred technical solution, the tunnel junction is selected from at least one of a tin oxide layer, a molybdenum oxide layer, a zinc oxide layer, a titanium oxide layer, a nickel oxide layer, an indium tin oxide layer, an aluminum-doped zinc oxide layer, and an antimony-doped tin oxide layer.
[0016] Another aspect of the present invention is to provide a method for preparing the above-mentioned laminated solar cell, the preparation method comprising the following steps:
[0017] S1: Using the first transparent conductive glass as a substrate, sequentially depositing an electron transport layer, a wide bandgap perovskite absorption layer, a hole transport layer and a metal counter electrode layer to obtain a wide bandgap perovskite battery;
[0018] S2: Using the second transparent conductive glass as a substrate, sequentially depositing an electron transport layer, a narrow bandgap perovskite absorption layer, a hole transport layer and a metal counter electrode layer to obtain a narrow bandgap perovskite battery;
[0019] S3: The wide bandgap perovskite cell prepared in step S1 and the narrow bandgap perovskite cell prepared in step S2 are stacked and compounded through a tunneling junction to obtain the all-perovskite laminated solar cell.
[0020] Beneficial effects of the present invention:
[0021] The tandem solar cell of the present invention not only improves the photoelectric conversion efficiency of the cell, but also enhances its stability and durability under different environmental conditions by innovatively introducing a perovskite absorption layer modified by a covalent organic framework (COF) material. This combination of structural design and material selection helps to improve the utilization rate of the solar spectrum by the cell, while reducing energy loss and extending the service life of the cell.
[0022] In general, the stacked solar cell of the present invention not only has excellent photoelectric conversion efficiency and good mechanical stability, but also ensures its long-term durability and stability under various environmental conditions. The overall comprehensive performance is strong, which can meet the high standard requirements of commercial applications and provide new possibilities for the development of solar cell technology. DETAILED DESCRIPTION
[0023] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0024] Example 1
[0025] The stacked solar cell of this embodiment includes a wide bandgap perovskite cell and a narrow bandgap perovskite cell and a tunnel junction arranged between the wide bandgap perovskite cell and the narrow bandgap perovskite cell; the wide bandgap perovskite cell and the narrow bandgap perovskite cell both include a perovskite absorption layer modified by a covalent organic framework material.
[0026] The method for preparing the stacked solar cell of this embodiment comprises the following steps:
[0027] S1: Using the first transparent conductive glass as the substrate, an electron transport layer, a wide bandgap perovskite absorption layer, a hole transport layer and a metal counter electrode layer are sequentially deposited to obtain a wide bandgap perovskite battery; the wide bandgap perovskite absorption layer is obtained by mixing a wide bandgap perovskite precursor solution and a covalent organic framework material uniformly and then heat treating. The wide bandgap perovskite precursor solution is obtained by mixing 14.2g of methylamine iodide, 7.8g of methyl bromide, 46.1g of lead iodide, 1.74g of cesium iodide, 1.68g of cesium chloride, 3.61g of lead bromide and 150mL of dimethyl sulfoxide solvent. The operating conditions of the heat treatment are annealing at 150°C for 60min. The thickness of the wide bandgap perovskite light absorption layer is 400nm.
[0028] S2: Using the second transparent conductive glass as the substrate, an electron transport layer, a narrow bandgap perovskite absorption layer, a hole transport layer and a metal counter electrode layer are sequentially deposited to obtain a narrow bandgap perovskite battery; the narrow bandgap perovskite absorption layer is obtained by mixing a narrow bandgap perovskite precursor solution and a covalent organic framework material uniformly and then heat treating. The narrow bandgap perovskite precursor solution is obtained by mixing 11.87g of tin powder, 7.8g of methyl iodide, 14.2g of methylamine iodide, 4.61g of lead iodide, 32.66g of stannous iodide, 1.57g of stannous fluoride and 150mL of dimethyl sulfoxide solvent. The operating conditions of the heat treatment are annealing at 100°C for 45min. The thickness of the narrow bandgap perovskite light absorption layer is 500nm.
[0029] The electron transport layer, hole transport layer and metal counter electrode layer in steps S1 and S2 of this embodiment are all made by conventional technical means in the art. For example, the electron transport layer is selected from titanium dioxide layer, the hole transport layer is selected from poly(3-hexylthiophene) (P3HT), and the metal counter electrode layer is selected from metallic silver. The thickness of the electron transport layer is 60 nm, the thickness of the hole transport layer is 60 nm, and the thickness of the metal counter electrode layer is 300 nm.
[0030] The covalent organic framework (COF) material is first subjected to an addition reaction of a trivinyl cyclic heterocyclic compound and hydroxyacrylamide, and then the reaction product undergoes a molecular self-assembly reaction with diisocyanate to form a covalent organic framework material with a three-dimensional network structure. Specifically, 0.1 mol of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane and 200 mL of solvent (N,N-dimethylformamide DMF) are first mixed evenly, and then 0.33 mol of N-hydroxymethyl acrylamide and 0.02 g of initiator ammonium persulfate (APS) are added, and the temperature is raised to 60°C for addition reaction, and the reaction time is controlled at 6 hours to ensure that the addition reaction is fully carried out. After the reaction is completed, the unreacted raw materials and initiators are removed by filtering and washing to obtain a cyclic hybrid compound intermediate containing hydroxyl and amide groups. Next, the intermediate product was dissolved again in 200 mL of DMF solvent, and then 0.12 mol of 4,4'-methylenebis(phenyl isocyanate) was added. Under nitrogen protection, the reaction system was slowly heated to 90°C and maintained at this temperature for molecular self-assembly reaction. The reaction time was controlled at 24 hours. During the self-assembly process, the hydroxyl group and the isocyanate group reacted to gradually form a three-dimensional network structure. After the reaction was completed, the by-products and unreacted diisocyanate were removed by filtration and washing, and finally the final covalent organic framework (COF) material was obtained by solvent exchange and vacuum drying.
[0031] S3: The wide bandgap perovskite cell prepared in step S1 and the narrow bandgap perovskite cell prepared in step S2 are stacked and compounded through a tunneling junction tin oxide layer to obtain the all-perovskite laminated solar cell. The thickness of the tunneling junction is 100 nm.
[0032] Comparative Example 1
[0033] The raw material composition and preparation steps of the preparation method of the perovskite-based thin-film stacked solar cell in this comparative example are basically the same as those in Example 1, except that, in the preparation method of this comparative example, neither the wide-bandgap perovskite absorption layer nor the narrow-bandgap perovskite absorption layer includes a covalent organic framework material.
[0034] The photoelectric conversion efficiency test of the perovskite-based thin-film stacked solar cell of Example 1 and Comparative Example 1 was carried out under a standard solar simulator, simulating the illumination condition of AM 1.5G, with an illumination intensity of 100 mW / cm 2 The test results show that the photoelectric conversion efficiency of the battery in Example 1 reaches 18.8%, which is 3.6 percentage points higher than 15.2% in Comparative Example 1. The short-circuit current density of the battery in Example 1 is 24.1 mA / cm 2, the open circuit voltage is 1.12V, and the fill factor is 0.77. In the stability test, after the battery has been running continuously for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 88%, while the battery performance of Comparative Example 1 drops to 76%. In addition, the moisture resistance test shows that the performance of the battery of Example 1 did not decrease significantly after running for 500 hours under 95% relative humidity, while the performance of the battery of Comparative Example 1 decreased by 10%. The heat resistance test also shows that the performance of the battery of Example 1 did not decrease significantly after running for 500 hours at 95°C, while the performance of the battery of Comparative Example 1 decreased by 12%. These test results show that by introducing a perovskite absorption layer modified with a covalent organic framework material, the battery of Example 1 has significantly improved photoelectric conversion efficiency, stability, and moisture and heat resistance.
[0035] Example 2
[0036] The raw material composition and preparation steps of the preparation method of the stacked solar cell of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the trivinyl cyclic heterocyclic compound adopts 2,4,6-trivinyl cycloboroxine instead of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane, the hydroxy acrylamide adopts N-(2-hydroxyethyl) acrylamide instead of N-hydroxymethyl acrylamide, the diisocyanate adopts p-phenylene diisocyanate instead of 4,4'-methylenebis(phenyl isocyanate), and the tunnel junction adopts a molybdenum oxide layer instead of a tin oxide layer.
[0037] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 19.2%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 89%; after running for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.
[0038] Example 3
[0039] The raw material composition and preparation steps of the preparation method of the stacked solar cell of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the trivinyl cyclic heterocyclic compound adopts 2,4,6-trimethyl-2,4,6-trivinylcyclotrisiloxane instead of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane, the hydroxy acrylamide adopts N-(3-hydroxypropyl) acrylamide instead of N-hydroxymethyl acrylamide, the diisocyanate adopts 1,1'-methylenebis(3,5-diethyl-4-isocyanatophenyl) instead of 4,4'-methylenebis(phenyl isocyanate), and the tunnel junction adopts a zinc oxide layer instead of a tin oxide layer.
[0040] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 20.5%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 90%; after operating for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.
[0041] Example 4
[0042] The raw material composition and preparation steps of the preparation method of the stacked solar cell of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the hydroxyacrylamide adopts N-(2-hydroxypropyl)methacrylamide instead of N-hydroxymethylacrylamide, the diisocyanate adopts 1,3-phenylenediisocyanate instead of 4,4'-methylenebis(phenyl isocyanate), and the tunnel junction adopts a titanium oxide layer instead of a tin oxide layer.
[0043] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 19.2%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 87%; after running for 500 hours under 95% relative humidity and 95°C, there is no obvious decline in performance.
[0044] Example 5
[0045] The raw material composition and preparation steps of the preparation method of the stacked solar cell of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the trivinyl cyclic heterocyclic compound adopts 2,4,6-trimethyl-2,4,6-trivinylcyclotrisiloxane instead of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane, the hydroxy acrylamide adopts N-(2-hydroxyethyl)methacrylamide instead of N-hydroxymethyl acrylamide, the diisocyanate adopts 1,3-bis(isocyanatomethyl)benzene instead of 4,4'-methylenebis(isocyanatophenyl ester), and the tunnel junction adopts a nickel oxide layer instead of a tin oxide layer.
[0046] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 18.8%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 89%; after running for 500 hours under 95% relative humidity and 95°C, there is no obvious decline in performance.
[0047] Example 6
[0048] The raw material composition and preparation steps of the preparation method of the stacked solar cell of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the trivinyl cyclic heterocyclic compound adopts 2,4,6-trivinyl cycloboroxine instead of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane, the diisocyanate adopts diphenylmethane diisocyanate instead of 4,4'-methylenebis(phenyl isocyanate), and the tunnel junction adopts an indium tin oxide layer instead of a tin oxide layer.
[0049] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 19.6%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 91%; after operating for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.
[0050] Example 7
[0051] The raw material composition and preparation steps of the preparation method of the stacked solar cell of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the hydroxyacrylamide adopts N-(3-hydroxypropyl)acrylamide, the diisocyanate adopts toluene diisocyanate instead of 4,4'-methylenebis(phenyl isocyanate), and the tunnel junction adopts an aluminum-doped zinc oxide layer instead of a tin oxide layer.
[0052] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 20.1%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 92%; after running for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.
[0053] Example 8
[0054] The raw material composition and preparation steps of the preparation method of the stacked solar cell of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the trivinyl cyclic heterocyclic compound adopts 2,4,6-trimethyl-2,4,6-trivinylcyclotrisiloxane instead of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane, the hydroxy acrylamide adopts N-(2-hydroxypropyl)methacrylamide instead of N-hydroxymethyl acrylamide, the diisocyanate adopts toluene diisocyanate instead of 4,4'-methylenebis(phenyl isocyanate), and the tunnel junction adopts an antimony-doped tin oxide layer instead of a tin oxide layer.
[0055] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 19.8%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 92%; after operating for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.
[0056] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.
Claims
1. An all-perovskite tandem solar cell, characterized in that: The all-perovskite tandem solar cell includes a wide-bandgap perovskite cell and a narrow-bandgap perovskite cell and a tunnel junction arranged between the wide-bandgap perovskite cell and the narrow-bandgap perovskite cell; at least one of the wide-bandgap perovskite cell and the narrow-bandgap perovskite cell includes a perovskite absorption layer modified by a covalent organic framework material.
2. The all-perovskite tandem solar cell according to claim 1, characterized in that: The covalent organic framework material modified perovskite absorption layer is obtained by uniformly mixing a perovskite precursor solution and a covalent organic framework material and then subjecting the mixture to heat treatment.
3. The all-perovskite tandem solar cell according to claim 1, characterized in that: The covalent organic framework material is firstly subjected to an addition reaction of a trivinyl cyclic heterocyclic compound and hydroxyacrylamide, and then the reaction product is subjected to a molecular self-assembly reaction with diisocyanate to form a covalent organic framework material with a three-dimensional network structure.
4. The all-perovskite tandem solar cell according to claim 1, characterized in that: The trivinyl cyclic heterocyclic compound is at least one of 2,4,6-trivinyl cycloboroxine, 2,4,6-trimethyl-2,4,6-trivinyl cyclotrisiloxane, and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisilazane.
5. The all-perovskite tandem solar cell according to claim 1, characterized in that: The hydroxyacrylamide is at least one of N-hydroxymethylacrylamide, N-(2-hydroxyethyl)acrylamide, N-(3-hydroxypropyl)acrylamide, N-(2-hydroxypropyl)methacrylamide and N-(2-hydroxyethyl)methacrylamide.
6. The all-perovskite tandem solar cell according to claim 1, characterized in that: The diisocyanate is at least one of 4,4'-methylenebis(phenyl isocyanate), p-phenylene diisocyanate, 1,1'-methylenebis(3,5-diethyl-4-isocyanatobenzene), 1,3-phenylenediisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, 1,3-bis(isocyanatomethyl)benzene, m-phenylenediisocyanate, and 1,3-bis(isocyanatomethyl)benzene.
7. The all-perovskite tandem solar cell according to claim 1, characterized in that: The wide bandgap perovskite cell comprises a wide bandgap perovskite absorption layer modified by a covalent organic framework material; the wide bandgap perovskite absorption layer is obtained by uniformly mixing a wide bandgap perovskite precursor solution and a covalent organic framework material, and then performing a heat treatment; the wide bandgap perovskite precursor solution is obtained by compounding methylamine iodide, methyl bromide, lead iodide, cesium iodide, cesium chloride, lead bromide and a solvent.
8. The all-perovskite tandem solar cell according to claim 1, characterized in that: The narrow-bandgap perovskite cell comprises a narrow-bandgap perovskite absorption layer modified by a covalent organic framework material; the narrow-bandgap perovskite absorption layer is obtained by uniformly mixing a narrow-bandgap perovskite precursor solution and a covalent organic framework material, and then subjecting the mixture to heat treatment; the narrow-bandgap perovskite precursor solution is obtained by compounding tin powder, methyl iodide, methylamine iodide, lead iodide, stannous iodide, stannous fluoride and a solvent.
9. The all-perovskite tandem solar cell according to claim 1, characterized in that: The tunnel junction is selected from at least one of a tin oxide layer, a molybdenum oxide layer, a zinc oxide layer, a titanium oxide layer, a nickel oxide layer, an indium tin oxide layer, an aluminum-doped zinc oxide layer, and an antimony-doped tin oxide layer.
10. A method for preparing the all-perovskite tandem solar cell according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1: Using the first transparent conductive glass as a substrate, sequentially depositing an electron transport layer, a wide bandgap perovskite absorption layer, a hole transport layer and a metal counter electrode layer to obtain a wide bandgap perovskite battery; S2: Using the second transparent conductive glass as a substrate, sequentially depositing an electron transport layer, a narrow bandgap perovskite absorption layer, a hole transport layer and a metal counter electrode layer to obtain a narrow bandgap perovskite battery; S3: The wide bandgap perovskite cell prepared in step S1 and the narrow bandgap perovskite cell prepared in step S2 are stacked and compounded through a tunneling junction to obtain the all-perovskite laminated solar cell.